Transcriptional reprogramming of xylem cell wall biosynthesis in tension wood. Issue 1 (2nd February 2021) - Liu, Baoguang; Liu, Juan; Yu, Jing; Wang, Zhifeng; Sun, Yi; Li, Shuang; Lin, Ying-Chung Jimmy; Chiang, Vincent L; Li, Wei; Wang, Jack P
Abstract: Tension wood (TW) is a specialized xylem tissue developed under mechanical/tension stress in angiosperm trees. TW development involves transregulation of secondary cell wall genes, which leads to altered wood properties for stress adaptation. We induced TW in the stems of black cottonwood ( Populus trichocarpa, Nisqually-1) and identified two significantly repressed transcription factor (TF) genes: class B3 heat-shock TF ( HSFB3-1 ) and MYB092 . Transcriptomic analysis and chromatin immunoprecipitation (ChIP) were used to identify direct TF–DNA interactions in P. trichocarpa xylem protoplasts overexpressing the TFs. This analysis established a transcriptional regulatory network in which PtrHSFB3-1 and PtrMYB092 directly activate 8 and 11 monolignol genes, respectively. The TF–DNA interactions were verified for their specificity and transactivator roles in 35 independent CRISPR-based biallelic mutants and overexpression transgenic lines of PtrHSFB3-1 and PtrMYB092 in P. trichocarpa . The gene-edited trees (mimicking the repressed PtrHSFB3-1 and PtrMYB092 under tension stress) have stem wood composition resembling that of TW during normal growth and under tension stress (i.e., low lignin and high cellulose), whereas the overexpressors showed an opposite effect (high lignin and low cellulose). Individual overexpression of the TFs impeded lignin reduction under tension stress and restored high levels of lignin biosynthesis in the TW. This study offers biological insights to further uncover how metabolism, growth, and stress adaptation are coordinately regulated in trees. Abstract : PtrHSFB3-1 and PtrMYB092 mediate transcriptional reprogramming of secondary cell wall biosynthesis during tension wood formation by direct and indirect transcription factor–DNA interactions with regulatory specificity.